A lithium tantalate reducing agent containing nanomaterials and a blackening process
By using lithium tantalate reducing agent composed of nanomaterials and the low-pressure annealing process of embedding, the problems of yellow light transmission, pyroelectric effect and poor processability of lithium tantalate wafers in high-frequency and fine finger products are solved, and the controllability and performance of the blackening process are improved.
Patent Information
- Application Number
- CN202411339303.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-09-25
AI Technical Summary
When making high-frequency and fine finger products, lithium tantalate chips have problems such as yellow light transmission, pyroelectric effect and poor processability, and the blackening process is not controllable enough, which affects the performance of the SAW filter.
Lithium tantalate reducing agent containing nanomaterials, specifically including FeSiAl microsheets, carbon nanospheres and Fe-C core-shell nanoparticles, are mixed evenly by electric stirring, combined with embedding method and low-pressure annealing process to blacken, and control the blackening temperature and time to achieve a controllable blackening process.
It realizes the simplification and controllability of the lithium tantalate blackening process, regulates the yellow light transmittance and resistivity of the wafer, improves the processability and performance of the wafer, and is suitable for high-frequency and fine-finger products of SAW filters.
Smart Images

Figure CN119221133B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of crystal materials, and in particular to a lithium tantalate reducing agent containing nanomaterials and a blackening process. Background Art
[0002] Lithium tantalate crystals have attracted much attention due to their unique optical and ferroelectric properties and are widely used in infrared detection devices, surface acoustic wave devices, high-frequency broadband filters, second harmonic generators, electro-optical Q-switched elements, laser frequency multipliers, etc. Lithium tantalate detectors have the characteristics of a wide operating temperature range, no need for refrigeration equipment, and low production costs, and have great research prospects.
[0003] As one of the key raw materials in the upstream of the RF filter industry chain for mobile communications, lithium tantalate is widely used as the substrate material of SAW filters, especially in the production of SAW device substrates with a frequency below 3GHz. No other material can replace it. Compared with lithium niobate, it has more stable physical and chemical properties and can detect high-power laser radiation. Thin film materials made of lithium tantalate have significant advantages as sensitive elements: the thickness of lithium tantalate film is easy to control, which greatly enhances the voltage detection rate and specific detection rate of the detector. Compared with crystals, lithium tantalate film materials are easy to prepare arrayed detectors, laying a good foundation for pyroelectric array detectors. At the same time, the easy repetitive production of lithium tantalate film greatly reduces the production cost, and the prepared detector also has good reproducibility, which is convenient for large-scale production of detectors. However, lithium tantalate also has some problems, such as yellow light transmittance and high pyroelectricity, which bring a lot of inconvenience to the manufacturing process of SAW devices. When making high-frequency and thin-finger products, the release of static charge can easily damage the wafer and burn the interdigital electrodes. In addition, the light transmittance of the material causes diffuse scattering on the back side of the wafer, which reduces the contrast of the lithographic circuits and leads to distorted line widths.
[0004] In order to solve these problems, a process of chemically reducing lithium tantalate wafers has emerged internationally, known as black film technology. Although the lithium tantalate black film obtained by blackening lithium tantalate can effectively reduce the pyroelectric effect of the wafer, overly black lithium tantalate wafers will affect the insertion loss of the SAW filter and easily lead to poor processing of the wafer. The blackening of lithium tantalate wafers needs to be controlled within a certain range. Therefore, it is of great significance to develop lithium carbonate reducing agents with good reducing properties and a process for controllable blackening process. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a lithium tantalate reducing agent and a blackening process containing nanomaterials. By relying on the strong lithium tantalate reducing agent containing nanomaterials and combining with supporting processes, the blackening process of lithium tantalate can be controlled and the blackening process can be simplified, while the yellow light transmittance and resistivity of the lithium tantalate wafer can be regulated.
[0006] The technical method adopted by the present invention to solve the technical problem is: a lithium tantalate reducing agent containing nanomaterials, including FeSiAl micron sheets, carbon nanospheres, and Fe-C core-shell nanoparticles. The FeSiAl micron sheets, carbon nanospheres, and Fe-C core-shell nanoparticles are uniformly mixed in a mass ratio of 90:5:5 and stirred by an electric stirrer.
[0007] Furthermore, the thickness of the FeSiAl micron sheet is 1 micron, the particle size of the carbon nanosphere is 100 nanometers, and the particle size of the Fe-C core-shell nanoparticle is 20 nanometers.
[0008] Furthermore, the stirring efficiency of the electric stirrer is 300 rpm, and the stirring time is 60 min.
[0009] On the other hand, the present invention provides a lithium tantalate wafer blackening process, wherein the blackening process uses a lithium tantalate reducing agent containing nanomaterials, and the specific steps include:
[0010] (1) selecting a lithium tantalate wafer and cutting the lithium tantalate wafer;
[0011] (2) placing the lithium tantalate wafer in alcohol for ultrasonic cleaning;
[0012] (3) preparing a reducing agent, uniformly mixing FeSiAl microsheets, carbon nanospheres and Fe-C core-shell nanoparticles in a mass ratio of 90:5:5, and stirring for 60 minutes using an electric stirrer;
[0013] (4) embedding the lithium tantalate wafer processed in step (2) into the reducing agent prepared in step (3), and placing it in a quartz boat, while ensuring that the upper and lower surfaces of the lithium tantalate wafer are covered with reducing agent powder;
[0014] (5) placing a quartz boat containing a reducing agent and lithium tantalate wafers in the central temperature zone of a horizontal vacuum tube furnace;
[0015] (6) starting the vacuum pump, reducing the gas pressure in the horizontal vacuum tube furnace to 0.5 Pa, introducing the reducing agent gas, and maintaining the pressure in the horizontal vacuum tube furnace at 0.5 Pa;
[0016] (7) After setting the blackening temperature, the blackening process is started, the temperature range of the central temperature zone of the horizontal vacuum tube furnace is set to 500 to 1000° C., and the heating is started at a heating rate of 10° C. / min until the temperature reaches the predetermined temperature of the central temperature zone, and the temperature is kept constant for 20 hours, while the pressure in the furnace tube of the horizontal vacuum tube furnace is kept at 0.5 Pa throughout the blackening process;
[0017] (8) After keeping warm for 20 hours, annealing is performed. After the annealing is completed, the furnace is allowed to cool naturally to room temperature, and the blackened lithium tantalate wafer is taken out.
[0018] Furthermore, in step (1), the length and width of the lithium tantalate wafer are 2cm*2cm and the thickness is 1mm.
[0019] Furthermore, the duration of ultrasonic cleaning in step (2) is 30 minutes.
[0020] Furthermore, in the step (5), the furnace tube in the horizontal vacuum tube furnace has a length of 120 cm and a diameter of 6 cm.
[0021] Furthermore, in step (6), the reducing agent gas is hydrogen, and the flow rate of the hydrogen is 200sscm.
[0022] Furthermore, the blackening temperature in step (7) is 500 to 1000°C.
[0023] In summary, the present invention provides a lithium tantalate reducing agent and blackening process containing nanomaterials, which controls the mixing ratio of the reducing agent FeSiAl micron sheets, carbon nanospheres, and Fe-C core-shell nanoparticles to form a composite strong reducing agent, and uses an embedding method and a low-pressure annealing process to blacken lithium tantalate wafers, thereby achieving a simple and controllable lithium tantalate blackening process. At the same time, by controlling the temperature of the central temperature zone, the effects of different blackening temperatures are guaranteed, thereby achieving the regulation of yellow light transmittance and resistivity of the lithium tantalate wafer. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a blackening process diagram and blackening sample diagrams of lithium tantalate wafers at different blackening temperatures;
[0025] Figure 2 This is a scanning electron microscope image of a blackened lithium tantalate wafer sample;
[0026] Figure 3 This is the XPS spectrum of the blackened lithium tantalate wafer sample;
[0027] Figure 4 This is a diagram of the transmittance and resistance parameters of blackened lithium tantalate wafers. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present application is further described in detail below in conjunction with specific implementation methods.
[0029] Embodiment 1
[0030] The lithium tantalate wafer was taken out, and the lithium tantalate wafer was cut into a size of 2cm*2cm in length and width and 1mm in thickness. The cut lithium tantalate wafer was placed in alcohol and ultrasonically cleaned for 30 minutes. Then, 90 parts of FeSiAl micron sheets with a thickness of 1 micron, 5 parts of carbon nanospheres with a particle size of 100 nanometers and 5 parts of Fe-C core-shell nanoparticles with a particle size of 20 nanometers were stirred for 60 minutes by an electric stirrer with a stirring efficiency of 300 revolutions / min to obtain a reducing agent. Then, the cleaned lithium tantalate wafer was embedded in the reducing agent, and at the same time, it was ensured that the upper and lower surfaces of the lithium tantalate wafer were covered with reducing agent powder, and then it was placed in a quartz boat. In the process, a quartz boat containing a reducing agent and a lithium tantalate wafer is placed in the central temperature zone of a horizontal vacuum tube furnace with a furnace tube length of 120 cm and a diameter of 6 cm. The vacuum pump is started. After the gas pressure in the horizontal vacuum tube furnace is reduced to 0.5 Pa, hydrogen with a flow rate of 200 sscm is introduced, and the pressure in the horizontal vacuum tube furnace is maintained at 0.5 Pa. The temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept constant for 20 hours. The continuous pressure is maintained at 0.5 Pa. After 20 hours of heat preservation, annealing is performed. At this time, the annealing temperature is 800°C. After the annealing is completed, the furnace is naturally cooled to room temperature, and the blackened lithium tantalate wafer (such as Figure 1 After testing, a scanning electron microscope image of the blackened lithium tantalate wafer was obtained (see Figure 2 ), the resistance of the lithium tantalate chip after blackening is 5.2×10 12 Ω, detected by light with a light wave frequency of 580nm, the transmittance of the lithium tantalate chip after blackening is 0.195%, and the blackening treatment is completed. The color of the lithium tantalate chip after treatment is pure black.
[0031] Embodiment 2
[0032] The lithium tantalate wafer was taken out, and the lithium tantalate wafer was cut into a size of 2cm*2cm in length and width and 1mm in thickness. The cut lithium tantalate wafer was placed in alcohol and ultrasonically cleaned for 30 minutes. Then, 90 parts of FeSiAl micron sheets with a thickness of 1 micron, 5 parts of carbon nanospheres with a diameter of 100 nanometers and 5 parts of Fe-C core-shell nanoparticles with a length of 20 nanometers were stirred for 60 minutes by an electric stirrer with a stirring efficiency of 300 revolutions / min to obtain a reducing agent. Then, the cleaned lithium tantalate wafer was embedded in the reducing agent, and at the same time, it was ensured that the upper and lower surfaces of the lithium tantalate wafer were covered with reducing agent powder, and then it was placed in a quartz boat. , place the quartz boat containing the reducing agent and the lithium tantalate wafer in the central temperature zone of a horizontal vacuum tube furnace with a furnace tube length of 120 cm and a diameter of 6 cm, start the vacuum pump, reduce the gas pressure in the horizontal vacuum tube furnace to 0.5 Pa, introduce hydrogen with a flow rate of 200 sscm, and maintain the pressure in the horizontal vacuum tube furnace at 0.5 Pa, increase the temperature to 1000°C at a heating rate of 10°C / min, and keep the temperature constant for 20 hours, and keep the pressure at 0.5 Pa. After 20 hours of heat preservation, annealing is carried out. At this time, the annealing temperature is 1000°C. After the annealing is completed, wait for the furnace to naturally cool to room temperature, and take out the blackened lithium tantalate wafer (such as Figure 1 f). After testing, the resistance of the blackened lithium tantalate wafer is 1.27×10 5 Ω, detected by light with a light wave frequency of 580nm, the transmittance of the lithium tantalate wafer after blackening is 0.1155%, and the blackening treatment is completed. The color of the lithium tantalate wafer after treatment is dark black.
[0033] It should be noted that in the drawings and tables of the present application, S500, S600, S700, S800, S900 and S1000 represent lithium carbonate wafer samples annealed at 500, 600, 700, 800, 900 and 1000°C, respectively. The embodiment of the present invention only selects the blackened lithium tantalate wafers when the central temperature zone of the horizontal vacuum tube furnace is set to 800°C and 1000°C. As for the blackening temperature, central temperature zone temperature and annealing temperature in the embodiment, specifically when the temperature of the central temperature zone is set to S600, that is, when the temperature of the central temperature zone is 600°C, the blackening temperature at this time is 600°C, and then annealing is performed after keeping warm for 20 hours, and the annealing temperature at this time is also 600°C. The resistance and error of the lithium tantalate wafer after blackening by the process of the present application are as follows:
[0034] As shown in Table 1:
[0035] Annealing temperature(℃) Resistance (Ω) Error(Ω) 550 <![CDATA[1.0×10 14 ]]> <![CDATA[1.0×10 13 ]]> 600 <![CDATA[9.0×10 13 ]]> <![CDATA[1.0×10 13 ]]> 650 <![CDATA[7.9×10 13 ]]> <![CDATA[5.0×10 12 ]]> 700 <![CDATA[7.3×10 13 ]]> <![CDATA[4.0×10 12 ]]> 750 <![CDATA[6.4×10 13 ]]> <![CDATA[1.0×10 12 ]]> 800 <![CDATA[5.2×10 13 ]]> <![CDATA[6.0×10 11 ]]> 850 <![CDATA[2.0×10 12 ]]> <![CDATA[1.0×10 11 ]]> 900 <![CDATA[2.0×10 9 ]]> <![CDATA[2.0×10 8 <!-- 3 -->]]> 950 <![CDATA[1.0×10 8 ]]> <![CDATA[1.0×10 7 ]]> 1000 <![CDATA[1.27×10 5 ]]> 12700
[0036] The light transmittance of the blackened lithium tantalate wafer obtained at different annealing temperatures is shown in Table 2:
[0037]
[0038]
[0039]
Claims
1. A lithium tantalate reducing agent comprising nanomaterials, characterized in that: The invention comprises FeSiAl micron sheets, carbon nanospheres and Fe-C core-shell nanoparticles, wherein the FeSiAl micron sheets, carbon nanospheres and Fe-C core-shell nanoparticles are uniformly mixed in a mass ratio of 90:5:5, the thickness of the FeSiAl micron sheets is 1 micron, the particle size of the carbon nanospheres is 100 nanometers, and the particle size of the Fe-C core-shell nanoparticles is 20 nanometers.
2. The lithium tantalate reducing agent containing nanomaterials according to claim 1, characterized in that: The FeSiAl micron sheets, carbon nanospheres and Fe-C core-shell nanoparticles are uniformly mixed by stirring with an electric stirrer.
3. The lithium tantalate reducing agent containing nanomaterials according to claim 2, characterized in that: The stirring efficiency of the electric stirrer is 300 revolutions / min, and the stirring time is 60 minutes.
4. A lithium tantalate wafer blackening process using the lithium tantalate reducing agent containing nanomaterials as claimed in claim 1, characterized in that: The process steps include: (1) Selecting a lithium tantalate wafer and cutting the lithium tantalate wafer; (2) Place the lithium tantalate wafer in alcohol for ultrasonic cleaning; (3) preparing a reducing agent, uniformly mixing FeSiAl microsheets, carbon nanospheres and Fe-C core-shell nanoparticles in a mass ratio of 90:5:5, and stirring with an electric stirrer for 60 min; (4) embedding the lithium tantalate wafer processed in step (2) into the reducing agent prepared in step (3), and placing it in a quartz boat, while ensuring that the upper and lower surfaces of the lithium tantalate wafer are covered with reducing agent powder; (5) Place the quartz boat containing the reducing agent and lithium tantalate wafer in the central temperature zone of the horizontal vacuum tube furnace; (6) Start the vacuum pump, reduce the gas pressure in the horizontal vacuum tube furnace to 0.5 Pa, introduce the reducing agent gas, and maintain the pressure in the horizontal vacuum tube furnace at 0.5 Pa; (7) After setting the blackening temperature, the blackening process is started. The temperature range of the central temperature zone of the horizontal vacuum tube furnace is set to 500 to 1000°C, and the heating is started at a heating rate of 10°C / min until the temperature reaches the preset temperature of the central temperature zone, and the temperature is kept constant for 20 hours. At the same time, the pressure in the furnace tube of the horizontal vacuum tube furnace is kept at 0.5 Pa during the entire blackening process; (8) After keeping warm for 20 hours, annealing is performed. After the annealing is completed, the furnace is allowed to cool naturally to room temperature and the blackened lithium tantalate wafer is taken out.
5. The lithium tantalate wafer blackening process according to claim 4, characterized in that: In the step (1), the length and width of the lithium tantalate wafer are 2 cm*2 cm and the thickness is 1 mm.
6. The lithium tantalate wafer blackening process according to claim 4, characterized in that: The duration of ultrasonic cleaning in step (2) is 30 minutes.
7. The lithium tantalate wafer blackening process according to claim 4, characterized in that: In the step (5), the furnace tube in the horizontal vacuum tube furnace has a length of 120 cm and a diameter of 6 cm.
8. The lithium tantalate wafer blackening process according to claim 4, characterized in that: In step (6), the reducing agent gas is hydrogen, and the flow rate of the hydrogen is 200 sscm.
9. The lithium tantalate wafer blackening process according to claim 4, characterized in that: The blackening temperature in step (7) is 500 to 1000°C.
Citation Information
Patent Citations
Method for machining lithium tantalate crystal substrates
CN107665813A
Preparation method for metal soft magnetic composite material, and metal soft magnetic composite material
CN109848428A
Cited By
FeCo-C-FeSiAl-coated HC powder applied to lithium tantalate blackening and preparation method of FeCo-C-FeSiAl-coated HC powder
CN121669954A